Towards Ensuring Credible Electoral Process in Nigeria’s Fourth Republic: Issues and Challenges: Menuju Penjaminan Proses Pemilu yang Kredibel di Republik Keempat Nigeria: Isu dan Tantangan - Femi Omotoso; John Nwaguru (Yayasan Nurul Musthafa, 2026)
All over the world, elections are the defining feature of democracy. Hence, a key component of democratic consolidation is electoral credibility, which guarantees legitimacy and reflection of the people's will in the outcomes of election results. Nigeria’s Fourth Republic has been faced with various attempts toward electoral reforms to ensure the credibility of elections since 1999. Nonetheless, persistent issues still threaten the integrity, and credibility of electoral procedures and outcomes. However, irrespective of the various electoral reform attempts/efforts, such as the Electoral Act 2022 and the introduction of technological tools like card readers, BVAS, and IReV, the electoral system’s credibility is still questionable. This paper critically examines the issues and challenges affecting electoral credibility in Nigeria such as electoral violence, vote commodification, weak electoral institution, judicial inconsistencies, voters’ apathy, political interference, technological limitations, among others. Theoretically, the democratic and institutional theories served as the theoretical foundations for this work. Methodologically, the study adopted survey research design as it utilised both primary and secondary sources of data. The primary source of data was derived through the use of questionnaire instrument, while the secondary source was derived from scholarly works in books, journals, magazines, INEC reports, electoral NGOs reports, among others. Data presentation and analysis was done both quantitatively and qualitatively. The results and findings proves that strengthening political institutions, improving election adjudication mechanisms, and enhancing INEC’s operational capacity are critical steps toward achieving free, fair, transparent elections and active citizen participation in Nigeria. Conclusively, this study submits that trust deficit in INEC, the judiciary, and security agencies must be tackled with decisive reforms, including technological upgrades, independent oversight, and civic education. [Di seluruh dunia, pemilihan umum merupakan ciri utama demokrasi. Oleh karena itu, salah satu komponen kunci dalam konsolidasi demokrasi adalah kredibilitas pemilu, yang menjamin legitimasi serta pencerminan kehendak rakyat dalam hasil pemilihan. Republik Keempat Nigeria telah menghadapi berbagai upaya reformasi pemilu sejak 1999 untuk menjamin kredibilitas pemilu. Namun demikian, berbagai persoalan yang terus berulang masih mengancam integritas dan kredibilitas prosedur serta hasil pemilu. Terlepas dari berbagai upaya reformasi pemilu seperti Undang-Undang Pemilu 2022 dan pengenalan perangkat teknologi seperti card reader, BVAS, dan IReV kredibilitas sistem pemilu masih dipertanyakan. Artikel ini mengkaji secara kritis isu dan tantangan yang memengaruhi kredibilitas pemilu di Nigeria, antara lain kekerasan pemilu, komodifikasi suara, lemahnya lembaga penyelenggara pemilu, inkonsistensi peradilan, apatisme pemilih, intervensi politik, keterbatasan teknologi, dan faktor lainnya. Secara teoretis, teori demokrasi dan teori institusional digunakan sebagai landasan analisis. Secara metodologis, penelitian ini menggunakan desain penelitian survei dengan memanfaatkan sumber data primer dan sekunder. Data primer diperoleh melalui instrumen kuesioner, sedangkan data sekunder berasal dari karya ilmiah berupa buku, jurnal, majalah, laporan INEC, laporan LSM pemantau pemilu, dan sumber lainnya. Penyajian dan analisis data dilakukan secara kuantitatif dan kualitatif. Hasil penelitian menunjukkan bahwa penguatan lembaga politik, perbaikan mekanisme penyelesaian sengketa pemilu, serta peningkatan kapasitas operasional INEC merupakan langkah krusial untuk mewujudkan pemilu yang bebas, adil, dan transparan serta mendorong partisipasi aktif warga negara di Nigeria. Secara keseluruhan, studi ini menegaskan bahwa defisit kepercayaan terhadap INEC, lembaga peradilan, dan aparat keamanan harus diatasi melalui reformasi yang tegas, termasuk peningkatan teknologi, pengawasan independen, dan pendidikan kewargaan.]